Reversible and Irreversible Effects of Electroporation on Contractility and Calcium Homeostasis in Isolated Cardiac Ventricular Myocytes. (28th October 2022) - Chaigne, Sébastien; Sigg, Daniel C.; Stewart, Mark T.; Hocini, Mélèze; Batista Napotnik, Tina; Miklavčič, Damijan; Bernus, Olivier; Benoist, David
Abstract : Background: Irreversible electroporation is an energy form utilizing high-voltage pulsed electric field, leading to cellular homeostasis disruption and cell death. Recently, irreversible electroporation has shown promising results for the treatment of cardiac arrhythmias. However, reversible and irreversible effects of pulsed electric field on cardiac myocytes remain poorly understood. Here, we evaluated the influence of a monophasic single electric pulse (EP) on the contractility, Ca 2+ homeostasis and recovery of cardiac myocytes. Methods: Isolated rat left ventricular myocytes were electroporated using single monophasic EP of different durations and voltages. Sarcomere length and intracellular Ca 2+ were simultaneously monitored for up to 20 minutes after EP application in Fura-2 loaded left ventricular myocytes. Lethal voltage thresholds were determined using 100 µs and 10 ms pulses and by discriminating cell orientation with respect to the electric field. Results: Electroporation led to an immediate increase in intracellular Ca 2+ which was dependent upon the voltage delivered to the cell. Intermediate-voltage EP (140 V, 100 µs) increased sarcomere shortening, Ca 2+ transient amplitude, and diastolic Ca 2+ level measured 1 minute post-EP. Although sarcomere shortening returned to pre-EP level within 5 minutes, Ca 2+ transient amplitude decreased further below pre-EP level and diastolic Ca 2+ level remained elevated within 20 minutes post-EP. Spontaneous contractions were observed after sublethal EP application but their frequency decreased progressively within 20 minutes. Lethal EP voltage threshold was lower in myocytes oriented perpendicular than parallel to the electric field using 100 µs pulses while an opposite effect was found using 10 ms pulses. Conclusions: Sublethal EP affected rat left ventricular myocytes contractility and disrupted Ca 2+ homeostasis as a function of the EP voltage. Moreover, EP-induced lethality was preceded by a large increase in intracellular Ca 2+ and was dependent upon the EP duration, amplitude and left ventricular myocytes orientation with respect to the electric field. These findings provide new insights into the effect of pulsed electric field on cardiac myocytes.